Volumetric Evaluation of Pharyngeal Airway after Functional Therapy. (18th February 2021) - Yıldırım, Ersin; Karaçay, Şeniz
Abstract : The aim of this study was to evaluate three-dimensional (3D) effects of Twin-block functional appliance (TB) on the pharyngeal airway by using cone beam computed tomography (CBCT). A total of 30 patients (14 females, 16 males; mean age 12.50 ± 1.23 and 12.83 ± 1.17 years, respectively) with skeletal Class II malocclusion were included in this study and were treated with TB. On the pretreatment (T1) and posttreatment (T2) CBCT scans, volumetric changes in the pharyngeal airway; SNA, SNB, and ANB angles; and bilateral effective mandibular (Co-Gn) and midfacial length (Co-A) were also evaluated. The statistical differences were accessed by Wilcoxon signed-rank tests, and Mann-Whitney U tests were used to analyze the scores of male and female subjects. In this study, an increase was observed in SNB and Co-Gn (p < 0.01 ) while a decrease in ANB and SNA (p < 0.01 and p < 0.05, respectively) was found. However, increase in midfacial length was not statistically significant (p > 0.05 ). In the evaluation of volumetric pharyngeal airway changes, statistically significant increases (p < 0.01 ) in the upper and lower division and total airway volume were determined. Gender differences were insignificant for all measurements (p > 0.05 ). Volumetric changes in the pharyngeal airway after functional therapy can be successfully evaluated by CBCT images. The anterior repositioning of the mandible by TB increases the mandibular length and pharyngeal airway volume in patients with retrognathic mandible.